Palatalization of the post-vocalic /s/: variationist analysis of the phonological transfer of L1 dialect in the acquisition of English as L2 - Lima, Priscila Evangelista Morais e (2015)
This study aims to identify the palatalization in the production of post-vocalic /S/  in  the  /S/t  context  by  paraibano  speakers  of  English  as  L2.  It  is  based on  Variationist Sociolinguistics  (LABOV,  2008  [1972])  and  in Acquisition of L2 (SELINKER, 1992; ELLIS, 2003 [1994]; BAYLE, 2007). The corpus is  comprised  of  18  informants  from  Paraiba  at  different  proficiency  levels. The  analysis  of  the  material  was  carried  out  with  the  use  of  the  GoldVarb X application (SANKOFF; TAGLIAMONTE; SMITH, 2005). The statistical analysis showed that the following variables: language level of proficiency, tonicity and preceding context were those more relevant to the implementation of palatalization.